Modeling the Smartphone Game to Improve Playersâ Focus Case Study of Game Dumb Ways to Die - Purnamasari, Elisa; Sanjaya, Ridwan (Soegijapranata Catholic University, 2014)
Commonly, playing a game is judged as an activity which spend a lot of time, money, and energy. Players usually spend their money to buy vouchers to play and also buy characters, weapons and equipments which provided in the game. Players who addicted to game mostly spend their time and energy to satisfy their desire to solve the challenge on a game.However, not all of games give the negative impacts. There are a lot of advantages which can be obtained by games, such as to train our memory, precision, speed, and even ability to get money from games.Â A game called âDumb Ways to Dieâ that can be found on smartphone is an example of game to increase speed and concentration of people who play it.There are a need to find some characteristics of a game which has positive effects for the players. Those characteristics can be formulated as the example of a good game. This paper will analyze the opinion and produce the conclusion from a survey of playing